Picture pocket atlas - "Bender, Lionel" (Kingfisher, London, 1991)
One of a series of information books for the younger reader. They are aimed at seven and eight-year-olds but, because of the high interest subjects and compact format, should also appeal to older children - particularly those who have reading difficulties.